A case of nodular cutaneous lupus mucinosis and literature review - Yuying YAO; Xiqing LI; Jianchi MA; Yijin LUO; Fengjie LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To report a case of nodular cutaneous lupus mucinosis and review relevant literature, in order to improve understanding of the disease. Methods We analyzed the clinical and histopathological features of a patient with nodular cutaneous lupus mucinosis. Results A 40 years old man presented with irregular erythema, with scales and partial atrophy on the cheeks, and multiple dense green bean-sized skin-colored nodules on his chest, back, abdomen, and proximal upper limbs. Antinuclear antibody was positive. Pathology of the early nodule showed dermal mucin deposition, and the pathology of later erythema was consistent with typical nodular cutaneous lupus mucinosis, with follicular keratotic plugs, epidermal atrophy, focal liquefaction of basal cells, and perivascular and peri-appendage infiltration of lymphocytes, as well as mucin deposition in the dermis. Direct immunofluorescence showed IgM and C3 positive at basement membrane. There was no renal nor hematologic involvement. The patient was diagnosed with nodular cutaneous lupus mucinosis and responded well to the treatments with systemic glucocorticoid in combination with hydroxychloroquine. Conclusions Although nodular cutaneous lupus mucinosis is a rare disease with unknown pathogenesis, dermatologists can still be able to make early diagnosis if they are familiar with its typical skin features and pathological changes. Dermatologists should strengthen their understanding of and be vigilance towards this disease.